IMPLEMENTATION OF FINANCING USING THE MUSYARAKAH SCHEME AT PT BANK ACEH SYARIAH AND ITS RELEVANCE TO SHARIA ECONOMIC LAW - Mawaddaturrahmah; Yuhasnibar (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This scientific article analyses the implementation of musyarakah financing at PT Bank Aceh Syariah and its relevance to Sharia Economic Law. Musyarakah, as one of the profit-sharing financing instruments, plays a crucial role in Islamic banking. This study examines the basic concepts, types, pillars, and principles of musyarakah within the framework of fiqh muamalah, as well as the regulatory framework in Indonesia, which includes laws, fatwas from the DSN-MUI, and guidelines from the OJK. Through a case study of PT Bank Aceh Syariah, this article describes the product, procedures, and implementation data, identifies challenges, and analyzes the alignment of practices with Sharia principles and the views of contemporary scholars. The research findings indicate that PT Bank Aceh Syariah has adopted musyarakah as its primary product, including Musyarakah Mutanaqisah, with structured procedures supported by a comprehensive regulatory framework. However, challenges such as customer dishonesty and a lack of understanding of the contract still exist. Nevertheless, adaptations in banking practices, such as the use of collateral, reflect efforts to balance Sharia compliance with modern banking prudence principles. This article concludes that the implementation of musyarakah at PT Bank Aceh Syariah is generally consistent with Sharia Economic Law. However, there is room for improvement in transparency and education to optimise the potential of this instrument in achieving equitable economic well-being.